Analisis Inovasi Kewirausahaan dalam Film Gampang Cuan - Fadli Faturrahman (Journal of New Trends in Sciences, 2025)
Innovation in entrepreneurship is not only limited to the creation of new products or services, but also includes the development of more efficient business models, more effective marketing strategies, and new ways of managing resources. The film "Gampang Cuan" offers a compelling depiction of the dynamics of entrepreneurship and innovation amidst family economic pressures. A thorough analysis of the film can provide valuable insights into how the characters in the film face financial challenges through the implementation of innovative entrepreneurial strategies. The film depicts how urgent needs can spark creativity and drive individuals to seek solutions outside conventional paths, resulting in small innovations that have a significant impact on their financial condition. This study aims to identify and analyze the various forms of entrepreneurial innovation that appear in the film, and how these innovations contribute to solving the financial problems faced by the characters. By analyzing elements such as opportunity identification, creative idea development, solution implementation, and adaptation to market changes, this study seeks to gain a deeper understanding of the entrepreneurial innovation process in a stressful context